Biological evaluation of amidine derivatives: In vitro cytotoxicity and cellular antioxidant capacity - Maria M. Pérez-Madrigal; Luis J. del Valle; Sara Armas Felipe; Cristina del Mar García Martín; José Ignacio Hernández García; César Saldías; Matías Funes; Carlos Alemán; MG Finn; David Díaz Díaz (PLoS ONE, 2026)
Amidines and related compounds are well known intermediates and protecting groups in organic synthesis. New methodological approaches and obvious structural and functional relevance to guanidines and imidazoles have also prompted interest in the biological activity of these compounds. Here we report a preliminary cytotoxicty evaluation of a set a formamidines and formamidine ureas obtained by convenient and modular synthetic routes. Standard epithelial (Vero, MDCK-SIAT) and fibroblast cell lines (COS-1, COS-7) were employed. All compounds were found to be relatively non-toxic, with LC50 values all in excess of 0.3 mM, but found to vary over the range of compound structures. Cell morphological changes were in good agreement with cell viability. Most of the compounds either suppressed the cellular antioxidant capacity or promoted reactive oxygen species (ROS) generation. The nontoxic nature of these molecules at low to moderate concentrations suggests that the amidine and formamidine urea functional groups are suitable for continued investigation in drug development.